Phytochemicals in Cancer Chemoprevention: Preclinical and Clinical Studies - Nitish Lekhak; Hitesh Kumar Bhattarai PhD (Cancer Control)
Phytochemicals, chemicals from plants, have garnered huge attention for their potential ability to prevent cancer. In vivo and preclinical models show that they do so often by affecting the hallmarks of cancer. Phytochemicals affect key pathways involved in the survival, genome maintenance, proliferation, senescence, and transendothelial migration of cancer cells. Some phytochemicals, namely antioxidants, can scavenge and quench reactive oxygen species (ROS) to prevent lipid peroxidation and DNA damage. They also trigger apoptosis by stopping the cell cycle at checkpoints to initiate the DNA damage response. Numerous in vitro and in vivo studies suggest that phytochemicals hinder cancer onset and progression by modifying major cell signaling pathways such as JAK/STAT, PI3K/Akt, Wnt, NF-kB, TGF-β, and MAPK. It is a well-known fact that the occurrence of cancer is in itself a very intricate process involving multiple mechanisms concurrently. Cancer prevention using phytochemicals is also an equally complex process that requires investigation and understanding of a myriad of processes going on in the cells and tissues. While many in vitro and preclinical studies have established that phytochemicals may be potential chemopreventive agents of cancer, their role in clinical randomized control trials needs to be established. This paper aims to shed light on the dynamics of chemoprevention using phytochemicals.